Pengaruh Pergerakan Pesawat Komersial Terhadap Pergerakan Penumpang di Bandara Blimbingsari Banyuwangi - Sabur, Fatmawati (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2019)
The need of public transportation is one of the communities needs that continue to grow in line with the increasing standard of economic life community. It shown on the role which the help movement accelaeration of information, goods, passengers, and especially in the tourism sector in order to attract tourists both domestic and foreign. of the three types of transportation that is land, sea, and air, by using air transportation is the right choice for the effectiveness and time efficiency, because it can be a solution of the problem of distance traveled in a relatively short time. The aim of this research is to find out how much the level of flight frequency and the volume of movement of airplane passengers at Blimbingsari Airport, Banyuwangi. This research is a non-experimental study, in the form of case studies of air traffic services, using descriptive and quantitative methods through the study of passenger movement data and the movement of commercial aircraft at the Blimbingsari airport in Banyuwangi. In this research, descriptive analysis contains data on the movement of commercial airplanes and passengers which occurred at Banyuwangi Airport in the period 2013-2018. Descriptive analysis of the results of the study can be known from observations of the data obtained during the study.